2013
DOI: 10.2516/ogst/2013186
|View full text |Cite
|
Sign up to set email alerts
|

Non-Aqueous and Crude Oil Foams

Abstract: D o s s i e rRe´sume´-Mousses non aqueuses et mousses pe´trolie`res -Les mousses produites a`partir de syste`mes non aqueux sont moins fre´quentes que les mousses a`base d'eau, mais elles jouent un roˆle important dans de nombreuses applications et proce´de´s industriels. La faible tension de surface des liquides a`base d'hydrocarbures limite l'adsorption des agents de surface classiques et par conse´quent diffe´rents compose´s et me´thodes doivent eˆtre conside´re´s afin de ge´ne´rer et de stabiliser les mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 76 publications
0
26
0
Order By: Relevance
“…Such foams are lighter than the oil alone and of current interest in foods due to the reduced oil/fat content. The unwanted foaming of petroleum or crude oil is a major problem during gas–oil separation and appropriate antifoams need to be designed which involve specific considerations not encountered in aqueous systems 24. Since the surface tension of most hydrocarbon-containing oils is low (<35 mN m –1 ) compared with that for water (72 mN m –1 at 25 °C), the driving force for adsorption of many hydrocarbon-based surfactants to their surface is significantly reduced 5…”
Section: Introductionmentioning
confidence: 99%
“…Such foams are lighter than the oil alone and of current interest in foods due to the reduced oil/fat content. The unwanted foaming of petroleum or crude oil is a major problem during gas–oil separation and appropriate antifoams need to be designed which involve specific considerations not encountered in aqueous systems 24. Since the surface tension of most hydrocarbon-containing oils is low (<35 mN m –1 ) compared with that for water (72 mN m –1 at 25 °C), the driving force for adsorption of many hydrocarbon-based surfactants to their surface is significantly reduced 5…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the use of fluorosilicones is commonly used in severe foaming cases . This is because they have similar properties which include low surface tension, strong defoaming ability, low dosage requirement, are hydrophobic, and do not react with other additives in the absorption solvent.…”
Section: Opportunities and Challenges Of Antifoams In Acid Gas Removalmentioning
confidence: 99%
“…Moreover, the use of fluorosilicones is commonly used in severe foaming cases. 110 This is because they have similar properties which include low surface tension, strong defoaming ability, low dosage requirement, are hydrophobic, and do not react with other additives in the absorption solvent. As such, a study that involved the synthesis and testing of fluorosilicone antifoam (which contains fluoroalkyl) has shown that this blended antifoam has a high affinity toward an aqueous or organic solution and demonstrated excellent and persistent antifoaming abilities.…”
Section: Opportunities and Challenges Ofmentioning
confidence: 99%
“…Owing to the low surface tension of organic solvents (typically ranging from 14 to 50 mN m −1 ), the adsorption of common foam stabilizers at the gas–liquid interface is energetically unfavorable and requires stabilizers with low surface energy (e.g., fluorinated and polydimethylsiloxane surfactants), asphaltenes, or fatty acid crystals [14b, 18a, 164] . As a result, the generation of oil‐based foams is much more challenging compared to aqueous foams [164d, 165] …”
Section: Advanced Conceptsmentioning
confidence: 99%